2023
DOI: 10.3389/fendo.2023.1135196
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-cytopathological subcategorization in thyroid nodules of atypia of undetermined significance/follicular lesion of undetermined significance using the TIRADS and Bethesda classifications

Amirhesam Babajani,
Saeed Rahmani,
Masoomeh Raoufi
et al.

Abstract: IntroductionBethesda category III – atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) is a heterogeneous class of the Bethesda system for thyroid nodules. In order to clarify the therapeutic road for clinicians, this category was subclassified based on the cytopathological features. In this study, we evaluated the risk of malignancy, surgical outcome, demographic characteristics, and correlation of ultrasound features with the final outcome in patients with thyroid n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Several studies have compared the ROM in which FNAC samples were subdivided based on whether they exhibited nuclear and/or architectural atypia, in which combined nuclear and architectural atypia has the highest ROM and is often shown to represent PTC on the histologic follow-up. However, isolated nuclear atypia has a somewhat lower ROM, and the ROM for cases with architectural atypia is generally much lower [9,13,14]. A similar trend has also been observed in thyroid FNA specimens from pediatric patients, where it was observed that the nuclear atypia as opposed to architectural atypia exhibited a clear-cut association with malignancy [15].…”
Section: Teasing Out "Atypia" In Thyroid Glandsupporting
confidence: 56%
See 1 more Smart Citation
“…Several studies have compared the ROM in which FNAC samples were subdivided based on whether they exhibited nuclear and/or architectural atypia, in which combined nuclear and architectural atypia has the highest ROM and is often shown to represent PTC on the histologic follow-up. However, isolated nuclear atypia has a somewhat lower ROM, and the ROM for cases with architectural atypia is generally much lower [9,13,14]. A similar trend has also been observed in thyroid FNA specimens from pediatric patients, where it was observed that the nuclear atypia as opposed to architectural atypia exhibited a clear-cut association with malignancy [15].…”
Section: Teasing Out "Atypia" In Thyroid Glandsupporting
confidence: 56%
“…1, 2) [1,[26][27][28]. The ROM for cases with architectural atypia in most instances is quite low, but not negligible [9,13,14].…”
Section: Architectural Atypiamentioning
confidence: 92%
“…On the other hand, the majority of these studies belong to the era before NIFTP and malignancy rates included NIFTP. However, in the post-NIFTP period, NIFTP is included in the malignant category in some of these studies [ 37 ], while in others, the status of NIFTP is not fully explained [ 16 , 26 , 38 , 47 ]. NIFTP was not even mentioned in several studies [ 8 , 25 , 48 ].…”
Section: Discussionmentioning
confidence: 99%